2020
DOI: 10.1038/s42003-020-01348-8
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin regulates fatty acid desaturation and fat deposition through MEF2C/miR222/SCD5 cascade in pigs

Abstract: Myostatin (MSTN), associated with the “double muscling” phenotype, affects muscle growth and fat deposition in animals, whereas how MSTN affects adipogenesis remains to be discovered. Here we show that MSTN can act through the MEF2C/miR222/SCD5 cascade to regulate fatty acid metabolism. We generated MSTN-knockout (KO) cloned Meishan pigs, which exhibits typical double muscling trait. We then sequenced transcriptome of subcutaneous fat tissues of wild-type (WT) and MSTN-KO pigs, and intersected the differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…CRISPR/Cas9-mediated HR was exploited to KO allele of MSTN in pig in our previous works [ 4 , 13 ]. We generated cloned MSTN-KO Meishan pigs followed by RNA-sequencing of backfat tissues to profile transcriptomes of MSTN-KO and WT pigs ( Figure 1a ).…”
Section: Resultsmentioning
confidence: 99%
“…CRISPR/Cas9-mediated HR was exploited to KO allele of MSTN in pig in our previous works [ 4 , 13 ]. We generated cloned MSTN-KO Meishan pigs followed by RNA-sequencing of backfat tissues to profile transcriptomes of MSTN-KO and WT pigs ( Figure 1a ).…”
Section: Resultsmentioning
confidence: 99%
“…Myostatin may also affect metabolism of adipose tissue by inhibiting differentiation of pre-adipocytes, and thus, both lipid accumulation and myostatin deficiency may promote browning of adipocytes (Li et al, 2011;Braga et al, 2013;Zhu et al, 2015). Ren et al (2020) identified a novel MSTN signal that regulates fat deposition by affecting fatty acid desaturation in MSTN-Knockout pigs via MEF2C/miR222/SCD5 (Ren et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…SCD gene: Stearoyl-coenzyme A desaturase gene ( SCD ) is a functional gene that encodes an important enzyme stearoyl-CoA desaturase necessary for the conversion of saturated fatty acids (SFAs) into monounsaturated fatty acids (MUFAs) [ 92 ]. The SCD gene has been associated with the fatty acid composition of porcine longissimus dorsi muscle [ 79 ], and acts as an important regulator of the genetic mechanism of lipid deposition and fatty acid synthesis in pigs [ 77 , 82 , 92 ]. Additionally, it is involved in the PPAR signalling pathway and is important for meat quality traits in pigs [ 72 ].…”
Section: Genes Involved In Fat Metabolism and Imf Accretion In Pigsmentioning
confidence: 99%
“…It is responsible for double muscling in cattle and Belgian domestic pig breeds, as well as in MSTN -knockout pigs [ 97 ]. Although naturally occurring MSTN mutation is yet to be established in pigs [ 98 ], it is reported to be associated with reduced fat metabolism [ 79 ], and significantly lower IMF content in MSTN mutant mouse lines [ 99 , 100 ]. Inducing MSTN mutation in pigs could result in an increase in longissimus dorsi muscle area, better lean meat yield, reduced backfat and carcass fat content in pigs [ 100 ].…”
Section: Genes Involved In Fat Metabolism and Imf Accretion In Pigsmentioning
confidence: 99%
See 1 more Smart Citation